Design on Vehicle Controller for Pure Electric Vehicle with Composite Power - ZHOU Mei-lan; YAN Wen-miao; GUO Jin-mei (Journal of Harbin University of Science and Technology)
Vehicle control unit is the key component of electric vehicle, the vehicle controller of pure electric vehicle with composite power is taken as the object of study. The composition of the vehicle control system is analyzed, the structure of the composite power is designed, the working mode and energy management control strategy of composite power is set, and the vehicle CAN communication network based on SAE J1939 standard protocol is designed. The CRUISE software is used to build the vehicle model of the pure electric vehicle with composite power. The effectiveness of energy allocation at the energy management control strategy for the composite power supply is verified. Then an experimental platform is built to test the whole vehicle controller. Experimental results show that the system design reliability of the vehicle controller and the energy control strategy rationality of the composite power is tested and verified.